Invasive surgical site infections after lung transplantation: contemporary risk factors and associated clinical outcomes - Manuela Carugati, MD; Sana Arif, MD; John Michael Reynolds, MD; John Carroll Haney, MD; Michael Edwards Yarrington, MD, MM; Katherine Young, MD; Deepika Kulkarni, MD; Alzora Benjamin; Katina Walline; Jonathan Huggins, MD, MSCE; Morgan Rosser, PhD; Samantha Morrison, PhD; et al. (JHLT Open)
Background: Invasive primary surgical site infections (IP-SSI) complicate lung transplant (LT) surgery. Identification of IP-SSI risk factors is critical to IP-SSI prevention. Methods: This single-center retrospective cohort study of adult patients who underwent LT at Duke University over a 5-year period (2017–2021) aimed to identify IP-SSI risk factors and describe outcomes associated with IP-SSI diagnosis. IP-SSI risk factors were identified using a Least Absolute Shrinkage and Selection Operator procedure for logistic regression. Results: IP-SSI occurred in 74/568 (13.0%) LT recipients. Restrictive lung disease, donor positive respiratory or blood cultures, operative time, post-transplant thoracic re-operation within 90 days of transplant, and ECMO by day 3 post-transplant were positively associated with IP-SSI. Obstructive lung disease, primary closure, and enhanced immunosuppression within 90 days of transplant were negatively associated with IP-SSI. Patients with IP-SSI were descriptively characterized by longer index transplant hospitalizations (92 vs. 22 days) and higher in-hospital (26.1% vs. 5.5%) and 1-year (20.3% vs. 12.1%) mortality rates than patients without IP-SSI. IP-SSI was significantly associated with 1-year mortality (HR 2.4, 1.3–4.3, p=0.003); however, the association was no longer significant (HR 1.4, 0.7–2.6, p=0.310) after adjusting for possible confounders. Conclusions: Conservative surgical approaches, targeted antimicrobial prophylaxis, and increased surveillance for patients with IP-SSI risks may play a critical roleto limit IP-SSI in the LT population.